Sphingomyelinases in a journey to combat arthropod‐borne pathogen transmission. Issue 12 (27th May 2021) - Rajendran, Kundave V.; Neelakanta, Girish; Sultana, Hameeda
Abstract : Ixodes scapularis ticks feed on humans and other vertebrate hosts and transmit several pathogens of public health concern. Tick saliva is a complex mixture of bioactive proteins, lipids and immunomodulators, such as I. scapularis sphingomyelinase ( Is SMase) ‐ like protein, an ortholog of dermonecrotoxin SMase D found in the venom of Loxosceles spp. of spiders. Is SMase modulates the host immune response towards Th2, which suppresses Th1‐mediated cytokines to facilitate pathogen transmission. Arboviruses utilize exosomes for their transmission from tick to the vertebrate host, and exosomes derived from tick saliva/salivary glands suppress C‐X‐C motif chemokine ligand 12 and interleukin‐8 immune response(s) in human skin to delay wound healing and repair processes. Is SMase affects also viral replication and exosome biogenesis, thereby inhibiting tick‐to‐vertebrate host transmission of pathogenic exosomes. In this review, we elaborate on exosomes and their biogenesis as potential candidates for developing novel control measure(s) to combat tick‐borne diseases. Such targets could help with the development of an efficient anti‐tick vaccine for preventing the transmission of tick‐borne pathogens. Abstract :